Soil Conservation in Brassica rapa chinensis L (Pakcoy) Growth - Nita Noriko; Rachmad Agustono; Risa Swandari Wijihastuti; Elya Novani; Nadiyah Isna Choirunnisa; Arief Pambudi (Jurnal Penelitian Pendidikan IPA, 2024)
Population increase has an impact on the procurement of food sources. Pakcoy is a vegetable that is in increasing demand. Farmers' response to this condition is to use excessive fertilizer and pesticides, thereby reducing soil fertility. The research aims to obtain a combination of fertilizer and humic acid, which is effective in cultivating B. rappa chinesis L., as well as soil conservation efforts. The methodology was experimental with Randomized Block Design (RBD) on four treatments, K, P1, P2, and P3. The dose of K was 150 g/5 m2, NPK 16:16:16, 1 kg/5 m2 dolomite, and 5 kg/5 m2 manure. The P1 treatment is the same as K but without NPK fertilizer. P2 and P3 treatments were reduced by 50% and 70% of NPK fertilizer, respectively, with the addition of humic acid. The research results show that P2 with local environmental conditions provides optimal results in terms of chlorophyll, stomata, and plant height. Soil fertility was shown by increasing pH to 6.6, K 281 ppm and P 509 ppm, Cation Exchange Capacity (CEC) 31.60 cmolc/kg, soil enzymes of 0.12 mg FDA g-1 soil d.w. h-1, an average number of earthworms of 17. The conclusion is that P2 fertilizer formulation can be applied to cultures as an anticipation of food security.